(6x+2)+2(3x-5)+(x+10)=

Simple and best practice solution for (6x+2)+2(3x-5)+(x+10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+2)+2(3x-5)+(x+10)= equation:


Simplifying
(6x + 2) + 2(3x + -5) + (x + 10) = 0

Reorder the terms:
(2 + 6x) + 2(3x + -5) + (x + 10) = 0

Remove parenthesis around (2 + 6x)
2 + 6x + 2(3x + -5) + (x + 10) = 0

Reorder the terms:
2 + 6x + 2(-5 + 3x) + (x + 10) = 0
2 + 6x + (-5 * 2 + 3x * 2) + (x + 10) = 0
2 + 6x + (-10 + 6x) + (x + 10) = 0

Reorder the terms:
2 + 6x + -10 + 6x + (10 + x) = 0

Remove parenthesis around (10 + x)
2 + 6x + -10 + 6x + 10 + x = 0

Reorder the terms:
2 + -10 + 10 + 6x + 6x + x = 0

Combine like terms: 2 + -10 = -8
-8 + 10 + 6x + 6x + x = 0

Combine like terms: -8 + 10 = 2
2 + 6x + 6x + x = 0

Combine like terms: 6x + 6x = 12x
2 + 12x + x = 0

Combine like terms: 12x + x = 13x
2 + 13x = 0

Solving
2 + 13x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 13x = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 13x = 0 + -2
13x = 0 + -2

Combine like terms: 0 + -2 = -2
13x = -2

Divide each side by '13'.
x = -0.1538461538

Simplifying
x = -0.1538461538

See similar equations:

| 4/7x=56 | | 3x+3=7x-23 | | x+4/5=-1/6 | | 160-36X=3.5Y | | 1/z-1/5z-1/4z=20/z+1 | | 4=-3/8+x | | 2-4(x+3)=7x-10 | | 4x/3-1=0 | | 5-(2x+7)= | | w-1/4=-5/8 | | (5x+7)=(15x-7) | | 6a+6a=5 | | 1/4+1=7 | | 2(3y+4)=4y+12 | | 31/2x11/4 | | -2+8(1-7n)= | | -u+14=3-14 | | X*36+Y*3.5=160 | | -3/4x=-19/2 | | x^4=2x^3+1 | | -v-1=4v+14 | | 13=-9+k | | 7x-(3x-7)=35 | | (-4^3y/x^-2y^2)^-2 | | -v-1=4w+14 | | 10=-15+r | | -3/4x=13/2 | | x^3(x-2)-1=0 | | -4=v+3/5 | | a^2x+(a-2)=(a+2)x | | 30=26+a | | 8-11/2 |

Equations solver categories